Forage Groups 2019
DOI: 10.5772/intechopen.83643
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Prediction of the Nutritive Value of Underutilised Forages as Potential Feeds for Ruminants

Abstract: The aim of the chapter was to evaluate and predict the nutritive and feeding value of unknown and underutilised forages. Underutilised forages were collected from various regions. Chemical composition and degradability of forages in the rumen were determined. A dataset was created bearing degradability parameters of feeds from 40 studies. Using the dataset, a step-wise regression procedure was used to develop regression equations to predict rumen degradability. Of the underutilised forages, crude protein conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Studies have concluded that the degradability of feeds in the rumen is greatly influenced by feed properties being digested, such as neutral detergent fibre and crude protein content [23]. The CP level of NPH in this study is sufficient to support the optimum activity of rumen microorganisms and can satisfy the maintenance requirement of the animals [24].…”
Section: Discussionmentioning
confidence: 67%
“…Studies have concluded that the degradability of feeds in the rumen is greatly influenced by feed properties being digested, such as neutral detergent fibre and crude protein content [23]. The CP level of NPH in this study is sufficient to support the optimum activity of rumen microorganisms and can satisfy the maintenance requirement of the animals [24].…”
Section: Discussionmentioning
confidence: 67%
“…The findings of the correlation analysis from this study suggest that there are possibilities of estimating degradability parameters (a, b, c and ED DM ) of a given forage using its chemical composition. Gerber [28] and Moyo et al [29] applied this principle in the estimation of degradability of protein and dry matter of feeds, respectively. Nsahlai et al [30] used similar approaches for the estimation of the nitrogen degradable parameters and dry matter degradability from chemical constituents for fresh leaves of multipurpose trees.…”
Section: Discussionmentioning
confidence: 99%
“…Feed sample properties that affect degradability were identified from literature including Bach et al [ 9 ] and Moyo et al [ 10 ]. Feed sample properties were particle size (mm), feed class, feed subclass, and feed compositional attributes (DM, dry matter; CP, crude protein; NDF, neutral detergent fibre, ADF, acid detergent fibre; HEM, hemicellulose, and ash all in g/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Microbial degradation is important in determining the digestibility [ 1 , 2 , 3 , 4 ] and rate of passage of fibrous feeds in the rumen, growth rate [ 5 ], and feed intake of ruminants [ 3 , 4 , 6 , 7 , 8 ]. Numerous studies [ 9 , 10 ] have concluded that the degradability of feeds in the rumen is greatly influenced by feed properties being digested such as neutral detergent fibre and crude protein content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation